2019
DOI: 10.1002/cssc.201901107
|View full text |Cite
|
Sign up to set email alerts
|

Intensified Electrocatalytic CO2 Conversion in Pressure‐Tunable CO2‐Expanded Electrolytes

Abstract: Multimolar CO2 concentrations are achieved in acetonitrile solutions containing supporting electrolyte at relatively mild CO2 pressures (<5 MPa) and ambient temperature. Such CO2‐rich, electrolyte‐containing solutions are termed as CO2‐eXpanded Electrolytes (CXEs) because significant volumetric expansion of the liquid phase accompanies CO2 dissolution. Cathodic polarization of a model polycrystalline gold electrode‐catalyst in CXE media enhances CO2 to CO conversion rates by up to an order of magnitude compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 68 publications
1
36
0
Order By: Relevance
“…CO), revealing total faradaic efficiencies that are less than unity (Supporting Information Table S1). Interestingly, we also observed similar faradaic efficiencies for CO 2 reduction to CO in our previous work using the same reactor setup (74% on Au 13 and 70% with Re(CO) 3 (bpy)Cl 14 ). This was attributed to the use of a single compartment electrochemical cell, which may allow some reduced species formed at the working electrode to be potentially oxidized at the counter electrode (or vice versa) resulting in lower faradaic yields.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…CO), revealing total faradaic efficiencies that are less than unity (Supporting Information Table S1). Interestingly, we also observed similar faradaic efficiencies for CO 2 reduction to CO in our previous work using the same reactor setup (74% on Au 13 and 70% with Re(CO) 3 (bpy)Cl 14 ). This was attributed to the use of a single compartment electrochemical cell, which may allow some reduced species formed at the working electrode to be potentially oxidized at the counter electrode (or vice versa) resulting in lower faradaic yields.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…12−14 We refer to these as CO 2 -eXpanded electrolytes because the liquid-phase volume expands with increasing CO 2 pressure (from 1.4−5.5 MPa) due to the dissolution of CO 2 (Supporting Information, Figure S1). In previous work, we observed (1) an order-of-magnitude enhancement of the catalytic current for CO 2 reduction to CO on heterogeneous catalysts (polycrystalline gold and copper), 12,13 (2) a significant enhancement of the catalytic rate for homogeneous (Re(CO) 3 (bpy)Cl (bpy = 2,2 -bipyridyl)) catalysts, 14 In this work, we demonstrate that the favorable properties of CXEs enhance the rate and selectivity of high-carbon content products via electrochemical carboxylation reaction pathways. Electrochemical carboxylation is an alternative approach to produce high-carbon-content carboxylic acids via the electrochemical coupling of CO 2 with organic compounds.…”
Section: ■ Introductionmentioning
confidence: 88%
“…Our recent findings [19,20] showed that significant quantities of CO 2 can be readily dissolved in acetonitrile (MeCN)c ontaining the supporting electrolyte tetrabutylammonium hexafluorophosphate, forming CXEs at CO 2 pressures of up to approximately 5.5 MPa. For example, the liquid-phasev olume is nearly doubled at approximately5MPa as ar esulto fC O 2 dissolution ( Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…[18] We recently reported the development of CO 2 -eXpanded Electrolytes (CXEs) as CO 2 -rich media for studies of electrochemistry and electrocatalysis. [19] These media leverage the mild criticalp roperties of CO 2 and are formed at modest pressures (1.5-5.5 MPa), engenderingd issolution of significant quantities of CO 2 (up to 15 m)i nto liquid acetonitrile-based electrolytes. Using this continuum of pressure-tunable media, we have reported observations of up to an order-of-magnitude enhancement in the CO 2 reduction rate by using aheterogeneous gold catalyst and modeled the pressure-dependent kinetics and mechanism of CO 2 reduction by both golda nd copper electrode catalysts in CXEs.…”
Section: Introductionmentioning
confidence: 99%
“…This can be ascribed to the fact that the presence of TEOA can trap photoinduced holes to prohibit the electron− hole recombination, while MeCN used as a solvent is beneficial for enhancing the CO 2 solubility in the system. 47 When CO 2 is replaced with N 2 , negligible CO product is detected, indicating that CO 2 is the essential resource of the CO product. Moreover, without Co(OH) 2 /H 2 Ti 6 O 13 , the reaction system only produces a very small amount of CO.…”
Section: Acs Applied Materialsmentioning
confidence: 99%